Mechanochemical synthesis of nanosized hydroxyyapatite powder and its conversion to dense bodies - Syed Abu Bakar, Sharifah Adzila; Sopyan, Iis; Abd Shukor , Mohamad Hamdi; Ramesh, Singh (Trans Tech Publications, 2011)
In this work, nanosized hydroxyapatite (HA) powder was synthesized via mechanochemical method by a dry mixture of calcium hydroxide Ca(OH)2 and di-ammonium hydrogen phosphate (NH4)2HPO4 powders. The effect of mechanochemical process on powder properties was investigated. Three rotation speeds of 170 rpm, 270 rpm and 370 rpm were chose with 15 hours milling time respectively. Characterization of nanopowders was accomplished by Fourier transform infra red (FTIR), X-ray diffraction (XRD) and nanosizer analysis. The green compacted powders with 200 MPa isostatically pressed were prepared and sintered in atmosphere condition at various temperatures ranging from 1150oC - 1350oC. The results showed that the rotation speed affected the obtained powders where the crystallite size was found increased with rotation speed (9 – 21 nm). In contrast, the particle size distribution decreased with rotation speed (322-192 nm). The sintering process has influenced the stability of powder by yielding TCP phase at a lower sintering temperature, 1150oC. However, powder synthesized at 370 rpm has showed a significant hardness, 5.3 GPa after compacted and sintered at 1250oC with the relative density of 95%. This phenomenon is believed to be related with the nanosize powder synthesized at high speed which has contributes the high strength of the sintered bodies.